2016
DOI: 10.1248/bpb.b16-00007
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Physicochemical Properties, and Transfection Activities of Tartaric Acid-Based Cationic Lipids as Effective Nonviral Gene Delivery Vectors

Abstract: In this work two novel cationic lipids using natural tartaric acid as linking backbone were synthesized. These cationic lipids were simply constructed by tartaric acid backbone using head group 6-aminocaproic acid and saturated hydrocarbon chains dodecanol (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…As the SSO used in this study does not match with any human gene, i.e., the SSO itself does not display any biological effect, suggesting that an increased cytotoxicity of transfection reagents occurred after SSO complexation. Interestingly, differing from what was observed in this work, several previous studies reported an attenuation of toxicity of the transfection reagents through complexation with nucleic acid [ 18 , 19 ]. The reasons for the different observation between our observation and these two publications need to be further studied, but it may due to: (1) difference in the type of genetic material.…”
Section: Discussioncontrasting
confidence: 99%
“…As the SSO used in this study does not match with any human gene, i.e., the SSO itself does not display any biological effect, suggesting that an increased cytotoxicity of transfection reagents occurred after SSO complexation. Interestingly, differing from what was observed in this work, several previous studies reported an attenuation of toxicity of the transfection reagents through complexation with nucleic acid [ 18 , 19 ]. The reasons for the different observation between our observation and these two publications need to be further studied, but it may due to: (1) difference in the type of genetic material.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, surface modification of liposomes with HA presents a strategy to endow liposomes with stealth properties in circulation without inducing accelerated blood clearance and the triggering of hypersensitivity reactions in certain sensitive individuals owing to complement activation after repeated administration. 62 Thus, HA, as an alternative to polyethylene glycol modification, represents an effective and promising strategy for the design and construction of future drug delivery systems that may greatly increase the utility of liposomes as drug delivery vehicles with prolonged circulation in vivo. Moreover, HA anchored at the surface of unilamellar liposomes clearly acts as a built-in cryoprotectant.…”
Section: Bioconjugate Chemistrymentioning
confidence: 99%
“…Compared to viral vectors, non-viral vectors possess lower immunogenicity, indicating their potential for widespread application worldwide [1]. Among non-viral vectors, cationic liposome-based lipoplexes are the most commonly used because of their ease of preparation [2]. However, there are still drawbacks to the use of lipoplexes, such as insufficient transfection efficiency and cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%